EFFECTIVENESS OF PARTICIPATORY, INNOVATIVE, COLLABORATIVE TRAINING MANAGEMENT IN IMPROVING MIDWIVES’ COMPETENCY IN WEST NIAS DISTRICT - Simatupang, Mei Yati; Gultom, Syawal; Rahman, Arif (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
Midwife competence is essential for improving maternal and child health services, especially in stunting prevention. Despite existing programs, many midwives do not meet required competency standards. This study evaluated the effectiveness of Participatory, Innovative, and Collaborative (PILAR)-based training in West Nias Regency. Using a quasi-experimental design, 52 midwives were divided equally into an intervention group receiving PILAR training and a control group without training. Competence was assessed via pretest and posttest evaluations. The intervention group’s mean score increased significantly from 33.42 (SD = 5.87) to 56.57 (SD = 5.22) (p = 0.027), while the control group showed minimal change, from 29.15 (SD = 3.17) to 31.50 (SD = 3.77) (p = 0.209). The gain score difference between groups was significant (p = 0.001), with the intervention group improving by 23.62 (SD = 6.76) versus 2.07 (SD = 2.08) in the control. PILAR-based training effectively enhances midwives’ competence, providing an innovative model to strengthen maternal and child health services.